2013
DOI: 10.4238/2013.september.19.6
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Microsatellite markers in Paulownia kawakamii (Scrophulariaceae) and cross-amplification in other Paulownia species

Abstract: ABSTRACT. Paulownia kawakamii is a fast-growing timber tree. In this study, 21 primer sets were developed using an enriched genomic library. The genetic diversity was measured in one P. kawakamii population. The number of alleles per locus ranged from 2 to 19. The observed and expected heterozygosities varied from 0.158 to 0.842 (mean = 0.421) and from 0.376 to 0.952 (mean = 0.771), respectively. All 21 loci were also polymorphic in closely related species (P. tomentosa, P. elongata, and P. fortunei). The desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Almost no genetic diversity existed in five microsatellite loci of two P. tomentosa populations in the LGWA. Our results contrast sharply with previous research in the tree's native range that found between two and six alleles at each locus we investigated here (Wang et al 2013). Our results, coupled with its high invasion success, suggest that P. tomentosa may be similar to other plant invaders with low genetic diversity that are facilitated by a few highly competitive genotypes and likely resulted from a single introduction (Poulin et al 2005;Taylor and Hastings 2004;Yu et al 2014;Zhang et al 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Almost no genetic diversity existed in five microsatellite loci of two P. tomentosa populations in the LGWA. Our results contrast sharply with previous research in the tree's native range that found between two and six alleles at each locus we investigated here (Wang et al 2013). Our results, coupled with its high invasion success, suggest that P. tomentosa may be similar to other plant invaders with low genetic diversity that are facilitated by a few highly competitive genotypes and likely resulted from a single introduction (Poulin et al 2005;Taylor and Hastings 2004;Yu et al 2014;Zhang et al 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Genomic DNA was extracted from each leaf sample using the DNeasy Plant Mini Kit reagents and protocol (Qiagen, Venlo, Netherlands). Five pairs of co-dominate, genus-specific microsatellite markers were used for genotyping analysis (Wang et al 2013). PCR was completed with a final volume of 15 µl containing 7 µl Master Mix (Promega, Madison, WI), 4 µl nuclease-free water, 1 µl 100X bovine serum albumin (BSA) (New England BioLabs, Ipswich, MA), 1 µl DNA template diluted to 8 ng/µl, 1 µl 10 µM reverse primer, 0.5 µl 10 µM forward primer, and 0.5 µl 10 µM fluorescent dye (FAM, VIC, NED).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation